Bisnis Olah Raga: Peran Bauran Pemasaran Pada Keberhasilan Usaha - Irwan Setiawan; Harmon Chaniago (Jurnal Riset Bisnis dan Investasi, 2017)
As a big city, Bandung needs sports area and facilities. However, in fact, just a little land available to be utilized. Seeing this potential market, some people who are keen to catch this opportunity are competing to set up the necessary sports facilities for residents. Futsal is one of the most famous. As a new business model, management needs various tactics and strategies to attract customers such as marketing mix strategy, yet the suitable marketing mix for sports business is still undiscoverable. For that reason, this study tries to find the dominant marketing mix that determines the success of a sports business venture, especially futsal, using the quantitative descriptive method. Collecting data from a total sample of 62 business units scattered in Bandung, the data from this sample then processed by the regression testing. The results prove that not all variants of the marketing mix futsal determine business success, critical success factors futsal sports business is largely determined by the quality of the product (futsal field) and supporting accessories.